2014
DOI: 10.4103/0973-1075.138401
|View full text |Cite
|
Sign up to set email alerts
|

The perception of trauma patients from social support in adjustment to lower-limb amputation: A qualitative study

Abstract: Introduction:The effect of amputation on an individual's psychological condition as well as family and social relationships is undeniable because physical disability not just affects the psycho-social adjustment, but also the mental health. When compared to normal people, such people are mostly experiencing social isolation. On the other hand, social support is known as the most powerful force to cope with stressful situations and it allows patients to withstand problems. The present study aims to explain unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
1
12
0
3
Order By: Relevance
“…One of the coping mechanisms was spirituality and use of prayer and worshiping God during difficult times. In Dadkhah et al (2014), researchers stated that participants sought help from their faith when confronted with the decision on lower limb amputation [ 35 ]. Another study reported that religious beliefs supported adaptability to chemical injury [ 36 ] or relying on religious beliefs for accepting the breast cancer diagnosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the coping mechanisms was spirituality and use of prayer and worshiping God during difficult times. In Dadkhah et al (2014), researchers stated that participants sought help from their faith when confronted with the decision on lower limb amputation [ 35 ]. Another study reported that religious beliefs supported adaptability to chemical injury [ 36 ] or relying on religious beliefs for accepting the breast cancer diagnosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on MS patients and their family caregivers showed that social support played an important role in managing the difficult and complicated conditions [ 19 , 45 , 46 ]. Dadkhah et al (2014) suggested that social support especially from friends and family played a significant role toward adaptability [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, they would not be able to continue their activity if such support did not exist. In their investigations, Torres and Solberg ( 2001 ) showed that the family's support led to higher self-efficacy, social cohesion, stress reduction, and health promotion among participants (Torres & Solberg, 2001 ; Valizadeh, Dadkhah, Mohammadi, & Hassankhani, 2014 ). In a study carried out by Berkman, social and family support and strong relationships were reported to be significant sources of individual health (Berkman, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with Valizadeh et al (2014) study that support by family and friends, the participants seem to benefit from the support of the peer group and this group plays a prominent role in adaptation with amputation. Individuals in a particular social network, especially in the peer groups such as groups consisted of patients with similar disease can help to other patients in finding a solution to the problem, authenticating, navigating to the information, creating positive emotions and comfort ( 22 ).…”
Section: Discussionmentioning
confidence: 99%